The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1460-9568.1995.tb01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Localization of Conventional Functional Magnetic Resonance Imaging and Magnetoencephalography

Abstract: The technique of functional magnetic resonance imaging (FMRI) allows the measurement of functional cerebral blood flow changes occurring with specific tasks. However, the spatial relationship between neuronal activity and functional cerebral blood flow changes is not known yet. This study compares the centre of neuronal activation (measured by magnetoencephalography) with that of the blood flow response (measured by FMRI) to unilateral motor stimulation in eight subjects. The results show a mean localization d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…In previously published reports the distances between main fMR imaging activity and the MEG dipole localization in preoperative localization studies have been shown to vary between 10 mm and 16 mm. [2,26] These differences correlate with our own investigations (unpublished data) in which we determined that the mean difference between fMR imaging and MEF/MEG in motor tasks is 14 mm. However, the measured blood oxygen level-dependent effect in fMR imaging tends to have its highest activity within or posterior to the central sulcus due to the individual venous architecture of the motor cortex.…”
Section: Discussionsupporting
confidence: 78%
“…In previously published reports the distances between main fMR imaging activity and the MEG dipole localization in preoperative localization studies have been shown to vary between 10 mm and 16 mm. [2,26] These differences correlate with our own investigations (unpublished data) in which we determined that the mean difference between fMR imaging and MEF/MEG in motor tasks is 14 mm. However, the measured blood oxygen level-dependent effect in fMR imaging tends to have its highest activity within or posterior to the central sulcus due to the individual venous architecture of the motor cortex.…”
Section: Discussionsupporting
confidence: 78%
“…For the contralateral SI, the disagreement was of the same order of magnitude as in previous studies comparing fMRI and MEG activation of the motor cortex [Sanders et al, 1996;Beisteiner et al, 1995]. For the other areas, the differences in localization were in some cases larger (see Table I).…”
Section: Comparison Of Fmri and Meg Localizations: Technical Aspectsmentioning
confidence: 66%
“…Localization of the hemodynamic responses could then give independent confirmation to electrophysiological source localization, and could be used to constrain the inverse problem solutions of MEG or EEG [Dale and Sereno, 1993;Hämäläinen et al, 1993;George et al, 1995;Ilmoniemi, 1995;Kwong, 1995;Simpson et al, 1995;Liu et al, 1998]. Recently, the location of the hand area of the primary motor cortex has been determined jointly with MEG and fMRI [Beisteiner et al, 1995;Sanders et al, 1996;Stippich et al, 1998]. These studies gave a mean difference in location of less than 10-16 mm between the two techniques.…”
Section: Introductionmentioning
confidence: 98%
“…However, the localization accuracy of FMRI is unknown at present; because of the various sources of artifacts, it might be in the millimeter or centimeter range. Quantitative data reviewed here showed an average FMRI-MEG difference of 8.8 mm in the study of Sanders et al [22] and an average FMRI-MEG difference 16.7 mm in the study of Beisteiner et al [24]. Although both groups used FLASH sequences and a 1.5-T Magnetom, important methodologic differences exist.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, the area of activation was much larger in the study of Beisteiner et al, and therefore individual FMRI pixel cannot be definitively attributed to pre-or postcentral activity. Data taken from the study of Beisteiner et al [24]. (b) Coronal section of the same subject.…”
Section: Discussionmentioning
confidence: 99%